ANALISIS BAMBU SEBAGAI STRUKTUR BALOK BANGUNAN RUMAH TINGGAL BERTINGKAT - Aditya Purnama; Imam Suyadi (JURNAL DAKTILITAS, 2022)
Abstract Bamboo material is a renewable natural product that can be obtained easily, cheaply, easily planted, grows fast, can reduce the effects of global warming, and has a very high tensile strength that can be competed with steel. Bamboo is a material that is commonly found in several villages and mountainous areas in Tulungagung, therefore bamboo material has a relatively cheap price. Loading reviews dead load and lives load. The analysis carried out in this study is loading, calculating the ultimate moment, normal force, and transverse force, then planning the bamboo beam against bending, tensile and compressive axial forces, and planning the shear of the bamboo beam. Then the bamboo beam is controlled against the combined axial bending load. Based on the results of the analysis and planning calculations, it was obtained that a bamboo beam with a stretch of 5 meters required 3 pieces of bamboo used to resist bending, and 2 pieces of bamboo needed as diagonal support. The bamboo used is bamboo with a diameter of 10 cm with a bamboo wall thickness of 1 cm. Keywords: Bamboo; beam; renewable; analysis; design Abstrak Material bambu merupakan produk hasil alam yang renewable yang dapat diperoleh dengan mudah, murah, mudah ditanam, pertumbuhan cepat, dapat mereduksi efek global warming serta memiliki kuat tarik sangat tinggi yang dapat dipersaingkan dengan baja. Bambu merupakan material yang banyak ditemui di beberapa desa dan daerah pegunungan di Tulungagung, maka dari itu material bambu memiliki harga yang relatif murah. Pembebanan meninjau beban mati dan beban hidup. Analisis yang dilakukan pada penelitian ini adalah pembebanan, menghitung momen ultimate, gaya normal, gaya lintang, kemudian merencanakan balok bambu terhadap lentur, gaya aksial tarik dan tekan, dan merencanakan geser balok bambu. Kemudian balok bambu dikontrol terhadap beban kombinasi aksial lentur. Berdasarkan hasil dari perhitungan analisis dan perencanaan diperoleh hasil balok bambu dengan bentangan 5 meter diperlukan bambu yang digunakan untuk menahan lentur sebanyak 3 buah, bambu yang diperlukan sebagai diagonal support sebanyak 2 buah. Bambu yang digunakan ialah bambu dengan diameter 10 cm dengan ketebalan dinding bambu 1 cm. Kata Kunci: Bambu; balok; renewable; analisis; perencanaan